2015
DOI: 10.1007/s00223-015-0063-9
|View full text |Cite
|
Sign up to set email alerts
|

Ladder-Climbing Training Prevents Bone Loss and Microarchitecture Deterioration in Diet-Induced Obese Rats

Abstract: Resistance exercise has been proved to be effective in improving bone quality in both animal and human studies. However, the issue about whether resistance exercise can inhibit obesity-induced bone loss has not been previously investigated. In the present study, we have evaluated the effects of ladder-climbing training, one of the resistance exercises, on bone mechanical properties and microarchitecture in high-fat (HF) diet-induced obese rats. Twenty-four rats were randomly assigned to the Control, HF + seden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
3
16
0
2
Order By: Relevance
“…Trabecular bone microarchitecture is generally considered an ideal index for predicting bone loss and bone structure deterioration [37]. Our findings also showed that obesity induced by an HFD is detrimental to trabecular bone of femur in rats.…”
Section: Discussionsupporting
confidence: 74%
“…Trabecular bone microarchitecture is generally considered an ideal index for predicting bone loss and bone structure deterioration [37]. Our findings also showed that obesity induced by an HFD is detrimental to trabecular bone of femur in rats.…”
Section: Discussionsupporting
confidence: 74%
“…These contradictory data can be explained by patient heterogeneity and study protocols, or different adiponectin significance according to the phase and severity of OA. Exercise was associated with increased adiponectin levels compared to high‐fat‐sedentary and control animals, with potential effect in preventing bone loss . Furthermore, mechanical loading up‐regulated adiponectin and its receptors in skeletal muscle .…”
Section: Adiponectinmentioning
confidence: 95%
“…In humans, high leptin levels observed in obesity were thought to be protective to bone fracture risk, but leptin resistant conditions and overweight lead to poor bone health outcomes . Exercise prevented bone loss and ameliorated bone biomechanical properties through regulation of leptin levels, suppression of inflammatory factors, and gain of skeletal muscle mass …”
Section: Leptinmentioning
confidence: 99%
“…Furthermore, the GLUT4 gene expression was also increased in these animals. Another study published by the same group of researchers [111] showed that serum levels of TNF-α and interleukin-6 were reduced with training, accompanied by an increase of adiponectin [112]. However, obese subjects undergoing strength training showed improvement in insulin sensitivity even without changes in serum levels of proinflammatory cytokines [113].…”
Section: How To Deal With the Enemymentioning
confidence: 99%